Application of Quantum Learning Education Model Through Contextual Approaches For Alpha Generations In Elementary School Children - Rizky Maydika Sampoerna; Nuril Af’idah; Niyyah Daniyatul Millah; Pita Nursiana (Proceedings of The ICECRS, 2020)
Alpha generation is the generation born between the years 2010-2024. Alpha generation is very vulnerable to the negative effects of digital influence if it is not matched by character education from an early age, because the rapid development of technology is more inherent in the era of alpha generation than the previous generation which enabled the lifestyle of the alpha generation to be strongly influenced by technological developments. In the sphere of education, the alpha generation is able to develop through a media search for references that are not only in the form of books, but can be obtained from journals, ebooks, internet sites and so on. With the rapid development of technology which also has an impact on the scope of alpha generation education, the author provides an innovative educational method for the alpha generation, namely "Application of the Quantum Learning Education Model Through a Constitutional Approach" in which this educational model aims to make students able to express their creativity by involving digital devices so that students are very productive in the use of digital media through a contextual approach. The hope is to familiarize students in the use of technology in accordance with the current digital era so that later they are able to create or produce something technological through the guidance of a contextual approach to students so as not to fall into the bad things because of the negative side of technological development. This learning model is very supportive of the learning process of alpha generation students currently born in conjunction with technological advancements. The author designed this educational model because the concept of education applied to millennials or other generations will no longer be suitable given the characteristics of the alpha generation are very different from other generations. This innovative education model is a collaboration between the quantum learning education model and the educational model of contextual approaches that are specifically designed for alpha generation. This educational model is formulated for the advancement of the quality of education in Indonesia by referring to the minimization of deficiencies between the two educational models and also the characteristics obtained in both are very supportive of the educational model needed in the alpha generation. The correlation of this educational model also trains creative activities so that elementary school students can create a creative product that benefits themselves and the environment.